Nilai Sosial dalam Novel Negeri 5 Menara Karya Ahmad Fuadi - Ichsan, Maulana; Nurhanisa, Linda (Literature Research Journal, 2023)
In today’s era, many individual tend to overlook the principles of etiquette. This poses a serious problem as humans inherently cannot live in isolation. Therefore, it is important to maintain relationships by adhering to the principles of social reality. This is crucial for preserving harmony within society. The novel "The Land of Five Towers" encompasses social values, making it interesting to explore. This research aims to depict the dynamics of social life as portrayed in the novel. Literary sociology is employed as the research method, with data extracted from quotations within the story. "The Land of Five Towers" serves as the primary source. Observational techniques are utilized for data collection, conducted between June 1st and 4th. The research location is determined conditionally. After the assessment, various social values are discovered, including tolerance, empathy, cooperation, discipline, empathy, democracy, loyalty, dedication, kinship, responsibility, and justice. Readers can cultivate an awareness of the importance of these values, facilitating their lives within society. Undoubtedly, these values are beneficial for individuals as they shape a courteous, wise, and integral personality.krama. Ini merupakan masalah serius karena sejatinya insan tidak bisa hidup sendiri. Maka dari itu, penting menjaga hubungan dengan melakukan prinsip realitas sosial. Hal ini demi menjaga keharmonisan di masyarakat. Novel Negeri 5 Menara mengandung nilai sosial sehingga menarik untuk diketahui. Penelitian ini pun bertujuan menggambarkan dinamika kehidupan sosial yang terjadi. Sosiologi sastra digunakan sebagai metode penelitian. Data diambil dari kutipan-kutipan pada isi cerita. Novel Negeri 5 Menara dijadikan sebagai sumbernya. Teknik observasi dilakukan untuk pengumpulan data. 1-4 Juni dimanfaatkan dalam pengambilan data. Sementara tempat penelitian dilakukan secara kondisional. Setelah pengkajian selesai ditemukan adanya nilai sosial, meliputi toleransi, kepedulian, kerja sama, disiplin, empati, demokrasi, kesetiaan, pengabdian, kekeluargaan, tanggungjawab dan keadilan. Pembaca dapat membangun kesadaran akan pentingnya nilai-nilai ini sehingga mempermudah kehidupannya di masyarakat. Tentunya nilai ini berguna bagi diri sendiri yang dapat membentuk kepribadian yang santun, bijaksana dan berintegritas.